The making of the defensive caste: Physiology, development, and evolution of the soldier differentiation in termites. Issue 6 (14th April 2020) - Miura, Toru; Maekawa, Kiyoto
Abstract: Termites (Blattodea, Termitoidea, or Isoptera) constitute one of the major lineages of eusocial insects. In termite societies, multiple types of functional individuals, that is, castes, perform divisions of labors to coordinate social behaviors. Among other castes, the soldier caste is distinctive since it is sterile and exclusively specialized into defensive behavior with largely modified morphological features. Therefore, many of the previous studies have been focused on soldiers, in terms of ecology, behavior, and evolution as well as developmental and physiological mechanisms. This article overviews the accumulation of studies especially focusing on the developmental and physiological mechanisms underlying the soldier differentiation in termites. Furthermore, the evolutionary trajectories that have led the acquisition of soldier caste and have diversified the soldier characteristics in association with the social evolution are discussed. Abstract : Termites possess soldiers in their colonies. This article overviews the recent advances of studies on physiological and developmental mechanisms underlying the soldier differentiation in termites, together with the evolutionary implications.